Pengaruh Pengetahuan Wajib Pajak, Administrasi Pajak, Tarif Pajak dan Sanksi Perpajakan terhadap Kepatuhan Pajak Pada Pelaku Usaha UMKM di Indonesia - Gandy Wahyu Maulana Zulma (Universitas Batanghari Jambi, 2020)
This study aims to test the determinants of tax compliance in small and medium enterprises (MSMEs) empirically, by considering several aspects such as tax knowledge, tax administration, tax rates, and tax sanctions in influencing the compliance of MSME taxpayers in Indonesia. The population and sample in this study focus on businesses with a turnover of less than 4.8 billion, which are included in the MSME sector. A total of 154 questionnaires were collected and can be used for further analysis through a series of statistical tests. The results showed that tax knowledge, tax administration, and tax sanctions have a positive effect on tax compliance in Indonesia. These findings indicate that better knowledge of tax, tax administration, and enforcement of fair and transparent tax sanctions can improve tax compliance.